IMPROVING STUDENTS` SPEAKING SKILL OF DESCRIPTIVE TEXTS THROUGH MIND MAPPING - Dina Syarifah Nasution; Nurul Indah Nasution (Journal of English Education and Linguistics, 2020)
This research aims to measure the implementation of Mind Mapping on Improving Students` Speaking Skill of grade X-2 TKJ of SMK N 1 Panyabungan, Mandailing Natal - Sumatera Utara. The method of this research was Classroom Action Research. The participant in this classroom action research was 44 students of grade X-2 TKJ of SMK N 1 Panyabungan, Mandailing Natal - Sumatera Utara. The instrument consisted of Mind Mapping Practice, Speaking test, observation sheet, and interviews. The data of this research was analyzed two methods of data analysis. Quantitative data analysis was used to examining and interpreting data from Mind Mapping practice and speaking test. The data taken from observation and interview was used qualitative data analysis. The result shows that (1) Mind Mapping better improves the students` Speaking Skill. This can be evidence from the students` means which better gradually improved in cycle one, and two, and (2) the researcher found that the changes of students` speaking skill are influenced by six factors, namely, interesting teaching media, interesting material, attractive classroom activities, enjoyable classroom management, attractive teacher`s approach, teacher strategy.